Mortality of Enlisted Men Who Served on Nuclear-Powered Submarines in the United States Navy. Issue 2 (17th February 2022) - Friedman-Jimenez, George; Kato, Ikuko; Factor-Litvak, Pam; Shore, Roy
Abstract : The increase in ischemic heart disease mortality was most likely due to active or passive exposure to tobacco smoke, which has been prohibited aboard submarines since 2011. These results support this policy as well as elimination of tobacco smoking and environmental tobacco smoke in other populations. Abstract : Objective: To describe the long-term mortality experience of a cohort of enlisted men who served on nuclear-powered submarines in the United States Navy and breathed recirculated filtered air for extended periods of time. Methods: In this historical cohort study we estimated standardized mortality ratios (SMRs) and used within-cohort Poisson regression analyses to address healthy worker biases. Results: Three thousand two hundred sixty three deaths occurred among 85, 498 men during 1, 926, 875 person-years of follow-up from 1969 to 1995. SMRs were reduced for most cause-of-death categories, prostate cancer had a twofold elevation. In within-cohort comparisons, prostate cancer mortality did not increase with duration of submarine service, but ischemic heart disease mortality increased 26% per 5 years of submarine service. Conclusions: Long periods of submarine service do not increase mortality in most cause-of-death categories. Increased mortality from ischemic heart disease likely reflects the effects of tobacco smoke.